Determinan Minat Berinfak Generasi Z di IAIN Padangsidimpuan - Nasution, Sahrial Ependi; Kamaluddin, Kamaluddin; Napitupulu, Rodame Monitorir (Journal of Islamic Social Finance Management, 2021)
Infaq is a fund issued voluntarily for an interest ordered by Islam. However, it has not been implemented optimally due to the constraints of students who do not have a fixed income and there has been a decrease in the number of donations, even though the number of students at IAIN Padangsidimpuan is increasing. The purpose of this study was to determine the effect of religiosity, income partially and simultaneously on the interest in giving infaq in z generation. This study uses quantitative research with primary data sources. Data collection techniques using interview techniques, questionnaires, and documentation with a sample size of 91 respondents and using random sampling. The data analysis used was validity test, reliability test, normality test, classical assumption test, determination coefficient test, hypothesis test and multiple linear regression analysis test. The results showed that the income variable did not partially influence the interest in giving in the z generation, while the religiosity variable had a partial effect on the interest in giving in the .z generation. Simultaneously, the religiosity variable, income together have an effect on the interest in giving in the z generation Keywords: Infaq, Interest, Income, Religiosity